The Role of Stakeholders in Enhancing the Public Service Agency's and Area Management's Performance Information Adequacy - Zunaidi, Achmad; Sutiono; Sudarso, Budi; Santoso, Kurniawan (Monas: Jurnal Inovasi Aparatur, 2024)
In addition to understanding the process for PNBP BLU income targets in the context of various BLU characteristics, the study intends to assess the role of stakeholders in the formulation of the performance of Public Service Agencies (BLU) involved in area management. This study focuses on the role of agents and principals in BLU performance decision making, as well as addressing problems connected to the application of input cost standards (SBM) and operational cost details in budgeting, in an effort to improve the efficiency and quality of BLU services. The findings of this study have the potential to significantly enhance BLU management in the field of area management and raise the standard of community services. This kind of research is exploratory and qualitative, concentrating on how performance is defined in relation to the budget. The research data were gathered from two sources: 1) interviews with six stakeholders who represented principals and 23 resource persons who served as agents for four BLUs; and 2) planning-budgeting materials that served as guidelines for BLU policy (including its rules). The study was carried out in 2022, from March to September. Based on the involvement of stakeholders, the study's findings identified two traits of BLU organizations within regional management clusters: 1) BLU exclusively as Satker; 2) BLU as a ministry in addition to Satker. Performance information is more explicitly formulated by BLU stakeholders, ministries, and Satker than by BLU alone. The more important BLU must take into account when planning and budgeting, the less focused and obviously linked the BLU service performance of regional management clusters is in the planning and budgeting documents.